Expression, purification, crystallization and crystallographic analysis of the N‐terminal domain of translocated intimin receptor. Issue 1 (1st January 2016) - Huang, Bing‐Yang; Gu, Jiang; Zhang, Yan‐Fang; Zhou, Jun‐Jun; Song, Xiao‐Yong; Lin, Yi; Li, Xin‐Min; Li, Lu
Abstract : Translocated intimin receptor (Tir) is an Escherichia coli ‐encoded protein that is transported into the host cell through a sophisticated bacterial type III secretion system (T3SS). Tir anchors the infected cell membrane twice using both its N‐ and C‐termini from inside the host cytoplasm for signalling. It plays a key role in enterohemorrhagic Escherichia coli (EHEC) infection, attaching and effacing (A/E) lesions and intracellular signal transduction. Here, the overexpression, purification and crystallization of its N‐terminal intracellular domain are reported. The crystal belonged to the orthorhombic space group I 41 22, with unit‐cell parameters a = b = 59.79, c = 183.11 Å. The asymmetric unit contained one molecule, with a solvent content of 51% and a V M of 2.55 Å 3 Da −1 .